1975
DOI: 10.1152/ajplegacy.1975.229.3.669
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of calcitonin in the newborn

Abstract: Calcitonin was injected in newborn rats and newborn lambs to study the metabolic effects of the hormone. Subcutaneous injection of salmon calcitonin (140 MRC U/kg) induced a clearing effect on plasma from suckling newborn rats that was naturally lactescent. A lower dose given by the same route (14 MRC U/kg) strongly decreased plasma triglyceride and amino acid levels in suckling newborn rats. This was mainly the result of gastric emptying inhibition. The gastrointestinal action of calcitonin in suckling newbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…So, STH, catecholamines and cortisol levels in blood increase under the effect of CT [13,14], i.e. CT also indirect can promote to the development of IR.…”
Section: Calcitonin and Insulin Resistancementioning
confidence: 99%
“…So, STH, catecholamines and cortisol levels in blood increase under the effect of CT [13,14], i.e. CT also indirect can promote to the development of IR.…”
Section: Calcitonin and Insulin Resistancementioning
confidence: 99%
“…The tissue distribution of radioactivity 4 h after forcefeeding illustrated the decrease in the absorption of labelled triolein. The distribution of radioactivity in control animals was very high in brown adipose tissue, but low in liver, kidney, muscle and bone ; 3 h after CT injection, the distribution of radioactivity for each organ studied was less in the CT group than in control animals (Garel, Barlet and Kervran, 1975). In newborn lambs, a physiological dose of porcine CT inhibited the elevation in plasma of total lipid, glucose and amino acid concentrations due to the first suckling period (fig.…”
mentioning
confidence: 92%
“…The hypocalcemic and hypophosphatemic effects of CT were more intense in the newborn rat than in rat fetus (Garel, 1969 ; Garel and Barlet,1974) ; the newborns were also more sensitive to the hormone since subcutaneous injection of a lower dose (1:5) markedly decreased plasma calcium and inorganic phosphorus concentrations . The injection of a large dose of CT in the suckling newborn rat had a clearing effect on plasma which was naturally lactescent (Garel, Barlet and Kervran, 1975). The clearing effect of CT was the result of a decrease in plasma lipids, as shown by the decrease in plasma triglyceride concentration ( fig.…”
mentioning
confidence: 99%
“…7). Garel, Barlet and Kervran (1975) have shown that CT decreased plasma triglyceride levels in suckling newborn rats mainly by inhibiting gastric emptying. It was also observed that a physiological dose of CT inhibited the elevation of plasma concentrations of total lipids, amino acids and glucose occurring after suckling in newborn lambs.…”
mentioning
confidence: 97%